Whole-Genome Sequencing Investigation of a Large Nosocomial Outbreak Caused by ST131 H30Rx KPC-Producing Escherichia coli in Italy - Aurora Piazza; Luigi Principe; Francesco Comandatore; Matteo Perini; Elisa Meroni; Vittoria Mattioni Marchetti; Roberta Migliavacca; Francesco Luzzaro (MDPI AG, 2021)
KPC-producing Escherichia coli (KPC-Ec) remains uncommon, being mainly reported as the cause of sporadic episodes of infection rather than outbreak events. Here we retrospectively describe the dynamics of a large hospital outbreak sustained by KPC-Ec, involving 106 patients and 25 hospital wards, during a six-month period. Twenty-nine representative KPC-Ec isolates (8/29 from rectal swabs; 21/29 from other clinical specimens) have been investigated by Whole-Genome Sequencing (WGS). Outbreak isolates showed a multidrug-resistant profile and harbored several resistance determinants, including blaCTX-M-27, aadA5, dfrA17, sulI, gyrA1AB and parC1aAB. Phylogenomic analysis identified the ST131 cluster 1 (23/29 isolates), H30Rx clade C, as responsible for the epidemic event. A further two KPC-Ec ST131 clusters were identified: cluster 2 (n = 2/29) and cluster 3 (n = 1/29). The remaining KPC-Ec resulted in ST978 (n = 2/29) and ST1193 (n = 1/29), and were blaKPC-3 associated. The KPC-Ec ST131 cluster 1, originated in a previous KPC-Kp endemic context probably by plasmid transfer, and showed a clonal dissemination strategy. Transmission of the blaKPC gene to the globally disseminated high-risk ST131 clone represents a serious cause of concern. Application of WGS in outbreak investigations could be useful to better understand the evolution of epidemic events in order to address infection control and contrast interventions, especially when high-risk epidemic clones are involved.